Applying Pan-Province-level Data Integration: Optimizing Stroke Fast Track Systems for Advanced Healthcare Delivery and Policymaking - Keeratikhajon, Warunee; Puttasima, Nuanlaaor (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2025)
Background: Stroke, a leading cause of death and disability worldwide, significantly impacts individuals and societies. One major challenge in public health management is providing a fast and efficient response to stroke cases. Fast-track stroke services have been established in many areas, but there are still problems that need to be addressed in certain regions. Integrating provincial-level data offers a crucial tool for effective stroke management and policymaking. This approach promises a comprehensive understanding of public health needs, improved service coordination, informed decision-making, and ultimately, enhanced service efficiency for stroke patients. Methodology: In this study, an exploratory research approach is employed, utilizing the pathway model to integrate Pan-Province-level Data for the development of optimized Stroke Fast Track Systems at the provincial level. Results: This study successfully establishes the model at the provincial level. The main features consist of: 1) Integrating and analyzing data from various sources, 2) Providing an overview of service delivery, 3) Facilitating activity seeking and support reception, and 4) Implementing a dashboard for collaborative work. The model, implemented as the "Collaborative Dashboard for tracking service pathways, seeking activities, support, monitoring, and mentoring," provides a comprehensive overview of service delivery, activity seeking, and support reception. Conclusion: Utilizing a pathway model to track the service pathway of stroke fast track through integrated data from all sectors or Pan data can lead to the successful development of the model for use in provincial-level service areas. The resulting model encompasses the pathways of service delivery, activity seeking, and support focus. It enables collaborative work among stakeholders to improve control and can inform policy-making for appropriate management moving forward.